Respuestas

2012-04-11T03:18:38+02:00

4x7 -27 +1   ->  multiplicacione y divisiones en parentesis

28 - 27 + 1 

     1+1 =  2

2012-04-11T03:42:46+02:00

 

FORMAS HIPERBÓLICAS 78 79 8081 82 8384 85 8687 88 8990 91 FORMAS ALGEBRAICAS DIVERSAS 92. 939495969798 99100a 100b101102 103104105 106107108109110 INTEGRALES DEFINIDAS 111 112113 L p /20 sen n   u   du = L p /20 cos n   u   du = 1 3 5   Á   ( n - 1)2 4 6   Á     n   p 22 4 6   Á   ( n - 1)3 5 7   Á     n   L q 0 e - au 2   du = 12  p a   ( a 7 0) L q  `0 u n e - u   du = ( n + 1) = n !   ( n   Ú 0) L du ( 2 au - u 2 ) n = u - a ( n - 2) a 2 ( 2 au - u 2 ) 2 - n + n - 3( n - 2) a 2 L du ( 2 au - u 2 ) n - 2 L ( 2 au - u 2 ) n   du = u - an + 1(2 au - u 2 ) n /2 + na 2 n + 1 L ( 2 au - u 2 ) n - 2   du L   duu n 2 au - u 2 = 2 au - u 2 a (1 - 2 n ) u n + n - 1(2 n - 1) a L   duu n - 1 2 au - u 2 L 2 au - u 2 u n   du = (2 au - u 2 ) 3/2 (3 - 2 n ) au n + n - 3(2 n - 3) a L   2 au - u 2 u n - 1   du L   2 au - u 2 u   du = 2 au - u 2 + a sen - 1   u - aa + C L u n   du 2 au - ug 2 = -   u n - 1 n 2 au - u 2 + (2 n - 1) an L   u n - 1 du 2 au - u 2 L u n 2 au - u 2   du = - u n - 1 (2 au - u 2 ) 3/2 n + 2 + (2 n + 1) an + 2 L u n - 1 2 au - u 2   du L duu 2 au - u 2 = sen - 1   u - aa + C L 2 au - u 2   du = u - a 2 2 au - u 2 + a 2 2sen - 1   u - aa + C L duu n au + b = - au + bb ( n - 1) u n - 1 - (2 n - 3) a (2 n - 2) b L   duu n - 1 au + b   si n   Z 1 L   duu au + b = 2 - b tan - 1   au + b - b + C   si b 6 0 L   duu au + b = 1 b ln 2 au + b - b au + b + b 2 + C   si b 7 0 L u n   du au + b = 2 a (2 n + 1)  a u n au + b - nb L   u n - 1   du au + b b L u   du au + b = 23 a 2 ( au - 2 b ) au + b + C L u n   au + b   du = 2 a (2 n + 3)  a u n ( au + b ) 3/2 - nb L u n - 1   au + b   du b L u au + b   du = 215 a 2 (3 au - 2 b )( au + b ) 3/2 + C L du ( a 2 u 2 ) n = 12 a 2 ( n - 1)  a u ( a 2 u 2 ) n - 1 + (2 n - 3) L du ( a 2 u 2 ) n - 1 b   si n   Z 1 L u ( au + b ) n   du = u ( au + b ) n + 1 a ( n + 1) - ( au + b ) n + 2 a 2 ( n + 1)( n + 2) + C   si n   Z   - 1, - 2 L u ( au + b ) - 2 du = 1 a 2   c ln ^ au + b + bau + b d + C L u ( au + b ) - 1   du = ua - ba 2 ln au + b + C L csc   u coth u   du = - csch u + C L sech u tanh u   du = - sech u + C L csch 2   u   du = - coth u   + C L sech 2   u   du = tanh u + C L coth 2   u   du = u - coth u + C L tanh 2   u   du = u - tanh u + C L cosh 2   u   du = 14senh 2 u + u 2 + C L senh 2   u   du = 14senh 2 u - u 2 + C L csch u   du = ln 2 tanh u 2 2 + C L sech u   du = tan - 1 senh u + C L coth u